Robust perfluorophenylboronic acid-catalyzed stereoselective synthesis of 2,3-unsaturated O-, C-, N- and S-linked glycosides - Tatina, Madhu Babu (Beilstein J Org Chem, 2019)
A convenient protocol was developed for the synthesis of 2,3-unsaturated C-, O-, N- and S-linked glycosides (enosides) using 20 mol % perflurophenylboronic acid catalyst via Ferrier rearrangement. Using this protocol, D-glucals and L-rhamnals reacted with various C-, O-, N- and S-nucleophiles to give a wide range of glycosides in up to 98% yields with mainly α-anomeric selectivity. The perflurophenylboronic acid successfully catalyzed a wide range of substrates (both glucals and nucleophiles) under very mild reaction conditions.